Adult education: An indispensable remedy for reduction of voter apathy in Anambra State - Ogbaka, L. C.; Ewelum, J. N.; Chieke, J. C.; Elekwa, B. (Journal of Research in Adult and Continuing Education, 2023)
This paper focuses on adult education as a remedy for reduction of voter apathy in Anambra State. Adult education is a lifelong process geared towards continuing development of people and the society at large. It is all education activities or programmes designed to equip individuals with veritable skills, capabilities, competencies, values and knowledge required to be informed and productive in life. This paper starts with an introduction and discusses certain concepts as well as programmes of adult education which could be used to reduce voter apathy such as civic education/ voter education,  political education and pre-election voter awareness campaigns. Futhermore, it discusses  the way forward and conclusions.
Keywords: Adult education; voter apathy